Induction of antibodies to the envelope protein of the human immunodeficiency virus by immunization with monoclonal anti-idiotypes. - Zaghouani, H (1991)
Anti-idiotypes that possess the internal image of antigen can induce protective humoral immunity toward microbes. Herein we demonstrate antigen mimicry by monoclonal anti-idiotypes of a distinct epitope of the human immunodeficiency virus (HIV) envelope protein that is defined by a synthetic peptide. This peptide, corresponding to amino acid residues 503-535 (peptide 503-535) of HIV-1 IIIB gp160, induced antibodies in three mammalian species that interacted with HIV-1 gp120 and inhibited in vitro syncytium formation caused by HIV-1, IIIB and MN isolates. Three monoclonal anti-idiotypes were generated against rabbit anti-gp120 antibodies specific for peptide 503-535. These anti-idiotypes recognize an interspecies cross-reactive idiotype expressed on mouse, chimpanzee, baboon, rabbit, and human anti-gp120 antibodies specific for peptide 503-535. The interaction with the cross-reactive idiotype is inhibited by synthetic peptide and HIV-1 gp160. Furthermore, rabbits immunized with the monoclonal anti-idiotypes produced antibodies that also bind HIV-1 gp120 and gp160 and recognized the epitope defined by peptide 503-535.